Development of Customer Loyalty Measurement Application using R Shiny - Oktavia Cintika; Warsito Budi; Kadarrisman Vincensius Gunawan Slamet (E3S Web of Conferences, 2023)
Shopee is a successful e-commerce platform in Southeast Asia today, becoming the leading choice for customers who want to shop online and has built loyal relationships with customers. Apart from Shopee, many other e-commerce companies also emphasize the importance of building customer loyalty as their primary goal. This research will explore the main factors that play a role in creating Shopee customer loyalty. By measuring customer loyalty, which refers to the variables of customer satisfaction, promotions, data security, and customer service. Through the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. Research data was obtained by distributing questionnaires to 180 customers who purchased on Shopee, distributed via TikTok. The research results show that two hypotheses were tested to understand the influence of variables on customer loyalty. The results show that customer satisfaction has a significant impact that exceeds other variables in creating customer loyalty. Promotion and data security also contribute positively, while customer service, although it has a positive effect, is not significant in influencing customer loyalty. The research conclusion emphasizes customer satisfaction as the primary strategy for maintaining and increasing customer loyalty, especially in the tight competitive environment in the e-commerce industry.